Pengaruh Literasi Keuangan dan Faktor Demografi terhadap Perilaku Menabung Gen Z, dengan Moderasi Lifestyle - Fahruna, Yulyanti; Dephary, Riatma Dita Perdana Sembiring; Mustika, Uray Ndaru; Syahputri, Anggraini (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Saving behavior among Generation Z in Indonesia tends to be relatively low. One of the contributing factors is their close relationship with technology and social media, which influences their financial habits. In addition, the generally low level of financial literacy also plays a role in shaping their saving behavior.This study aims to examine whether financial literacy significantly influences the saving behavior of Generation Z in Indonesia and whether lifestyle serves as a moderating variable in this relationship. The research employs a quantitative approach, with data collection and analysis carried out using the SmartPLS 4.0.9.9 software. The testing includes assessments of validity, reliability, the coefficient of determination, and significance tests.The results indicate that financial literacy and demographic factors have a significant impact on saving behavior. However, lifestyle does not moderate the relationship between financial literacy and saving behavior, as its influence is limited. This research is expected to serve as a reference for policymakers to enhance financial literacy and promote saving behavior among the public.